NOVEL POLYSILAMETHYLENOSILANES - NEW PRECURSORS FOR SILICON-CARBIDE - JUNG, IN; LEE, GH; SUK, MY; YEON, SH (KOREAN CHEMICAL SOC, 1991)
Novel polysilamethylenosilanes (PSMS) were prepared by Wurtz type co-condensation of various mixtures of 2,4,4,6-tetrachloro-2,6-dimethyl-2,4,6-trisilaheptane (TSH) and dimethyldichlorosilane (D). When TSH was incorporated more than 25 mole%, PSMS polymers were soluble in common organic solvents probably due to the polycarbosilane linkage brought from TSH. The molecular weights of the polymer were measured by gel permeation chromatography and showed higher molecular weight with high TSH content. The thermal gravimetric residues increased as TSH contents increased. These properties suggested that PSMS polymers could be useful as ceramic precursors for silicon carbide.
Keywords: HIGH-TENSILE STRENGTH; HIGH YOUNGS MODULUS; POLYCARBOSILANE; FIBER